2017
DOI: 10.1038/s41598-017-07321-6
|View full text |Cite
|
Sign up to set email alerts
|

Employing high-frequency alternating magnetic fields for the non-invasive treatment of prosthetic joint infections

Abstract: Treatment of prosthetic joint infection (PJI) usually requires surgical replacement of the infected joint and weeks of antibiotic therapy, due to the formation of biofilm. We introduce a non-invasive method for thermal destruction of biofilm on metallic implants using high-frequency (>100 kHz) alternating magnetic fields (AMF). In vitro investigations demonstrate a >5-log reduction in bacterial counts after 5 minutes of AMF exposure. Confocal and scanning electron microscopy confirm removal of biofilm matrix c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 50 publications
2
58
0
Order By: Relevance
“…This sample preparation protocol has been described previously for SEM imaging of biofilms [31]. The dried specimens were mounted on aluminum stubs, sputter coated with gold/palladium, and examined using the scanning electron microscope operating at 5kV (Zeiss ΣIGMA VP Field Emission Scanning Electron Microscope, Carl Zeiss Microscopy LTD, UK) [4]. …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This sample preparation protocol has been described previously for SEM imaging of biofilms [31]. The dried specimens were mounted on aluminum stubs, sputter coated with gold/palladium, and examined using the scanning electron microscope operating at 5kV (Zeiss ΣIGMA VP Field Emission Scanning Electron Microscope, Carl Zeiss Microscopy LTD, UK) [4]. …”
Section: Methodsmentioning
confidence: 99%
“…It was observed that a 4–5 log reduction in bacterial count (measured as colony forming units (CFU)) could be achieved within 5–7 minutes of heat treatment (20W of power) when Pseudomonas aeruginosa or Staphylococcus aureus biofilms were grown on metal washers [4]. This study also revealed a potential synergistic relationship between the antimicrobial ciprofloxacin and AMF exposures in the treatment of P. aeruginosa biofilms.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations